Ulus Devlet Basın ve Siyaset (Tek Parti Döneminde Halkevleri ve Ün Dergisi) - Gökmen, Mustafa (Academician Publishing Book DOI Portal, 2023)
1789’da Fransız Devrimi ile Avrupa’da başlayan ve dünyaya yayılan milliyetçilik hareketi, çok uluslu siyasi otoriteleri yıkarak ulus devletlerin kurulmasının yolunu açmış ve dünyadaki tüm imparatorlukları olumsuz etkilemiştir. Devletin ulus devlet olarak kurulması, örgütlenmesi ve güçlendirilmesi uzun ve zorlu bir süreçti. Çünkü Türkiye Cumhuriyeti’nin ulus devlet olarak inşası sürecinde, devrimlerle birlikte siyasi ve sosyal yapıda birçok yenilik, değişim ve gelişme yaşanmıştır. Kurulan devlet, bazı sıkı sıkıya bağlı ilkelere dayanmaktadır. Bu ilkeler Cumhuriyetçilik, Milliyetçilik, Devrimcilik, Devletçilik, Laiklik ve Popülizmdir. Cumhuriyetin kurucu kadroları, 1930’ların başından itibaren Cumhuriyet değerlerini ve halk devrimlerini benimsemek amacıyla yeni bir aşamaya geçtiler. Bu amaçla, yeni devletin hedefleri doğrultusunda eğitim kurumlarında düzenlemeler yapıldı. İlköğretimden yükseköğretime kadar bir dizi değişiklik gerçekleştirildi. Aynı zamanda, yetişkin nüfusun eğitim ve kültür düzeyini yükseltmek için Toplum Merkezleri kuruldu. 1930’ların ilk yarısından itibaren iktidar partisi, devrimlerin ve yeni düzenin kamuoyuna ifade edilmesinde doğrudan veya dolaylı olarak önemli bir araç olarak medya organlarını kullandı. Bu araştırmada, örnek yayın olarak Isparta Toplum Merkezi tarafından yayınlanan Ün dergisi (1934-1949) incelenmiştir. Dergide ulus devlet üzerine yayınların özellikle Cumhuriyet Bayramı ile aynı zamana denk gelen sayılarda yoğunlaştığı gözlemlenmiştir. Dergide, hem Atatürk döneminde hem de İnönü döneminde yayın çizgisinin kesintisiz olarak korunduğu görülmüştür. Çalışmada yer alan tüm veriler, nitel veri analizi yöntemiyle incelenmiştir. Araştırma sonucunda bulgulara ulaşılmıştır. Dergideki yayınların, dönemin hakim anlayışını ortaya koyduğu söylenebilir. ÜN yerel bir dergi olmasına rağmen, ulusal konulara ilişkin yayınlarında devletin hakim anlayışına bağlı kalmaktadır. The Nationalism movement, which started in Europe in 1789 with the French Revolution and spread to the world, negatively affected all empires in the world, paving the way for the establishment of nation states by destroying multinational political authorities. The Nationalism movement, which started in Europe in 1789 with the French Revolution and spread to the world, negatively affected all empires in the world, paving the way for the establishment of nation states by destroying multinational political authorities. The establishment, organization and strengthening of the state as a nation state involved a long and difficult process. Because In the process of building the Republic of Turkey as a nation-state, along with revolutions, there have been many innovations, changes and developments in the political and social structure. The established state is based on some strictly adhered to principles. These principles are Republicanism, Nationalism, Revolutionism, Statism, Secularism and Populism. The founding cadres of the Republic moved to a new stage since the beginning of the 1930s in order to adopt the values ​​of the Republic and the revolutions by the people. For this purpose, regulations have been made in educational institutions in line with the goals of the new state. A number of changes were made from primary education to higher education. At the same time, Community Centers were established to raise the education and cultural level of the adult population. Since the first half of the 1930s, the ruling party has used the media organs, directly or indirectly, as an important tool in the public expression of the revolutions and the new order. In this research, Ün the magazine published by Isparta Community Center (1934-1949) was examined as a sample publication. It has been observed that the publications on the nation state in the journal are especially concentrated in the issues that coincide with the Republic Day. In the journal, it was seen that the publication line was maintained uninterruptedly both in the Atatürk period and in the İnönü period. Again, all the data included in the study were analyzed by qualitative data analysis. As a result of the research, the findings were reached. It can be said that the publications in the journal reveal the prevailing understanding of the period. Although ÜN is a local journal, it adheres to the prevailing understanding of the state in publications on national issues.